2015
DOI: 10.1002/ajmg.a.36944
|View full text |Cite
|
Sign up to set email alerts
|

Kaufman oculocerebrofacial syndrome in sisters with novel compound heterozygous mutation in UBE3B

Abstract: A pair of sisters was ascertained for multiple congenital defects, including marked craniofacial dysmorphisms with blepharophimosis, and severe psychomotor delay. Two novel compound heterozygous mutations in UBE3B were identified in both the sisters by exome sequencing. These mutations include c.1A>G, which predicts p.Met1?, and a c.1773delC variant, predicted to cause a frameshift at p.Phe591fs. UBE3B encodes a widely expressed protein ubiquitin ligase E3B, which, when mutated in both alleles, causes Kaufman … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 26 publications
2
20
0
Order By: Relevance
“…KOS is a rare type of the BMRS, caused by biallelic mutations of the ubiquitin protein ligase E3B gene (Basel‐Vanagaite et al, ; Flex et al, ). Beyond the short and narrow palpebral fissures and intellectual disability, affected individuals typically show hypotonia, microcephaly, sparse and thin hair, sparse and laterally broad eyebrows, malformed ears and/or external meati, and feeding difficulties (Basel‐Vanagaite et al, , ; Flex et al, ; Kariminejad et al, ; Pedurupillay et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…KOS is a rare type of the BMRS, caused by biallelic mutations of the ubiquitin protein ligase E3B gene (Basel‐Vanagaite et al, ; Flex et al, ). Beyond the short and narrow palpebral fissures and intellectual disability, affected individuals typically show hypotonia, microcephaly, sparse and thin hair, sparse and laterally broad eyebrows, malformed ears and/or external meati, and feeding difficulties (Basel‐Vanagaite et al, , ; Flex et al, ; Kariminejad et al, ; Pedurupillay et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Kaufman oculocerebrofacial syndrome (KOS), a rare autosomal recessive type of the BMRS, was first described in 1971, but it was not until 2012 that its genetic cause was discovered via the identification of biallelic mutations in the ubiquitin ligase E3B encoding gene UBE3B (Basel‐Vanagaite et al, ; Flex et al, ; Kaufman et al, ) With only 15 published patients with biallelic UBE3B mutations reported so far, knowledge on the phenotypic and molecular characteristics of KOS is still expanding. (Basel‐Vanagaite et al, , ; Flex et al, ; Kariminejad et al, ; Pedurupillay et al, ) Apart from the original four patients of Kaufman, five patients with the clinical diagnosis of KOS have been reported between 1971 and 2013 (Briscioli, Manoukian, Selicorni, Livini, & Lalatta, ; Figuera, Garcia‐Cruz, Ramirez‐Duenas, Rivera‐Robles, & Cantu, ; Jurenka & Evans, ; Murano, ). The patient of Briscioli et al () had no blepharophimosis and was later subject of UBE3B sequencing by Flex et al () but no disease‐causing mutation was identified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3, 5 It is also worth noting that a subset of the UBE3B variants that occur upstream of the HECT domain are either missense, truncating or frameshift and hence, are perceived to compromise the enzymatic activity of the HECT domain or the function of UBE3B protein. Even though UBE3B is expressed in the brain and craniofacial structures during embryonic development, 2 it is unclear how mutations in UBE3B lead to KOS.…”
Section: Discussionmentioning
confidence: 99%
“…1–5 There is marked variability in the phenotype. The variability in the phenotype has caused some patients to be initially diagnosed as having other entities such as Toriello-Carey syndrome or a “new syndrome”.…”
Section: Introductionmentioning
confidence: 99%